TINY HOUSE: REFLECTION ON PARTICIPATORY ACTION RESEARCH AS A TOOL OF INQUIRY IN THE KAMPUNG COMMUNITY - Nuraeny, Elita; Paramitha, Amira; Herlily, Herlily (UI Scholars Hub, 2020)
At the end of 2015, the government of Jakarta declared a river normalization program to widen both banks of the Ciliwung River and increase its channel capacity. Approximately 15 meters of inspection road was to be constructed immediately. To avoid eviction, 223 households in Kampung Anak Kali (KAKC) reduced their domestic spaces by shearing five meters off their houses, forcing them to allocate less space for daily activities, including cooking, bathing, and washing. Living in a tight space, constructing a tiny house is a necessity, not a lifestyle choice. The residents of KAKC, therefore, live in limited areas for survival, and each develops a house with unique characteristics to suit their needs. In response, a community engagement program was conducted in 2019 to redevelop houses and solve the domestic space issue in KAKC. Through four case studies, the project implemented Participatory Action Research (PAR) to share knowledge in spatial occupation between homeowners and professional architects. The result of the community engagement project is various spatial adaptations in small spaces with architectural consideration in safe, health, and financial affordability. This paper investigates deeper into how the project performed PAR as a tool of inquiry and criticizes the result. In the end, this paper concluded that PAR, which is established as a method in community-based projects, can be applied in a smaller subsystem such as a household.